The Level of Knowledge of Students of Singaperbangsa Karawang University About How First AID When A Sports Injury Occurs - Alie, Ahmad Mudzakkir; Baqir, Chesta Adabi; Hidayat, Fadhillah Maulana (UNIVERSITAS NEGERI MAKASSAR, 2024)
This study aims to evaluate the level of knowledge of Singaperbangsa University Karawang students regarding first aid during sports injuries. The method used was quantitative with data collection through questionnaires distributed to active students, both athletes and non-athletes. The results showed that 100% of the 29 respondents had a good understanding of first aid in injury situations. However, there was a significant difference between student-athletes and non-athletes, where student-athletes had a higher level of knowledge (66.7%) compared to non-athletes (44.4%). These findings emphasize the importance of improving the understanding of first aid for all students, especially for those involved in sporting activities, to reduce the risk of more serious injuries. Recommendations are given to conduct training and seminars to improve students' knowledge and skills in providing first aid when injuries occur.